Factors influencing the quality of induction of labour at a district hospital in Tshwane: A qualitative study - Mathevula, Rirhandzu Friddah; Mosesane-Kuduntwane, Gofaone Precious (Orapuh Journal, 2026)
Introduction Induction of labour is a widely used obstetric intervention performed when continuation of pregnancy poses risks to maternal or fetal health. In South Africa’s public healthcare sector, induction rates remain high. Outcomes are closely linked to the quality of care, which is influenced by clinical practices, health system factors, and resource constraints. Associated risks include failed induction, uterine hyperstimulation, and emergency caesarean delivery. Purpose This study aimed to explore factors influencing the quality of induction of labour practices among midwives at a district hospital in Tshwane, South Africa. Method A qualitative exploratory descriptive design was employed. The study was conducted at a busy district hospital in the Tshwane District, Gauteng Province. Purposive sampling was used to recruit 16 female midwives qualified in basic and advanced midwifery, aged 27–64 years, each with at least two years of experience and direct involvement in labour induction. Data were collected between July and August 2023 through in-depth semi-structured interviews. Interviews were audio-recorded with participants’ consent and transcribed verbatim. Data were analysed using the thematic analysis approach described by Braun and Clarke. Results Analysis revealed one overarching theme, systemic barriers compromising induction quality, comprising three subthemes derived from participant responses. Five participants reported (1) overbooking and heavy caseloads leading to rushed procedures; seven participants highlighted (2) increasing induction volumes alongside fixed staffing levels; and seven participants identified (3) inadequate institutional support, including limited access to guidelines, insufficient training, and lack of multidisciplinary support. These factors collectively undermine clinical decision-making, adherence to protocols, and overall quality of care, while also contributing to midwife burnout and adverse maternal–fetal outcomes. Conclusion The findings highlight systemic challenges at a district hospital in Tshwane that compromise the quality of labour induction. These results underscore the need for urgent interventions, including strengthened institutional support, implementation of a scheduling cap of three inductions per day, staffing reviews, and the establishment of quarterly induction of labour (IOL) review mechanisms.